2003
DOI: 10.1159/000068904
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Open-Labeled, Non-Inferiority Study between Ciclopiroxolamine 1% Cream and Ketoconazole 2% Foaming Gel in Mild to Moderate Facial Seborrheic Dermatitis

Abstract: Background: Topical ketoconazole (KC) is considered a standard treatment for seborrheic dermatitis. In a placebo-controlled, double-blind clinical study, we demonstrated that antifungal ciclopiroxolamine (CIC) 1% cream was effective in mild to moderate facial seborrheic dermatitis. Objectives: We report here the results of a randomized, open-labeled clinical study comparing CIC 1% cream and KC 2% foaming gel in patients with mild to moderate facial seborrheic dermatitis, using a non-inferiority trial design. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
0
26
0
2
Order By: Relevance
“…It was decided not to use a double-blind, double-dummy design, partly for reasons discussed by the authors of a similar trial [25]. Such a protocol would have been difficult to implement given the different appearances of the two ointments, thereby compromising the blinding of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It was decided not to use a double-blind, double-dummy design, partly for reasons discussed by the authors of a similar trial [25]. Such a protocol would have been difficult to implement given the different appearances of the two ointments, thereby compromising the blinding of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ciclopirox shows a good efficacy/tolerance ratio in mild to moderate SD [61]. Ciclopirox inhibits prostaglandin and leukotriene synthesis [62].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…A randomized, open labeled clinical study was conducted by Chosidow et al [42] to compare ciclopirox olamine 1% cream and ketoconazole 2% foaming gel in patients with mild to moderate facial SD. The authors found that at the end of the maintenance phase, treatment response to ciclopirox olamine was greater than to ketoconazole in both intention-to-treat (ITT) and per protocol (PP) populations.42 However, while the group applying ciclopirox was using it twice daily, the group applying ketoconazole gel was using it only twice a week during the initial phase.…”
Section: Topical Antifungals Available For Sdmentioning
confidence: 99%